Organ donation in trauma victims: A systematic review and meta-analysis. Issue 6 (June 2018) - Cameron, Adam; Erdogan, Mete; Lanteigne, Sara; Hetherington, Alexandra; Green, Robert S.
Abstract : BACKGROUND: Although trauma patients represent a large pool of potential organ donors (PODs), the donor conversion rates (DCRs) in this population are unclear. Our primary objective was to synthesize published evidence on DCRs in trauma patients. As a secondary objective, we investigated factors that affect organ donation (OD) in the trauma population. METHODS: We searched four electronic databases (PubMed, Embase, Web of Science, and Cochrane Library) and gray literature for articles on OD in trauma patients (PROSPERO 2017: CRD42017070388). Articles were excluded if it was not possible to calculate the DCR (actual organ donors divided by PODs). We pooled DCRs and performed subgroups analysis by trauma subpopulation, patients' age, and study publication date. RESULTS: We identified 27 articles with a total of 123, 142 participants. Cohorts ranged in size from 28 to 120, 512 patients (median, 132), with most studies performed in the United States. Conversion rates among individual studies ranged from 14.0% to 75.2% (median, 49.3%). All 27 studies were included in the meta-analysis. We found a pooled DCR of 48.1% using the random effects model. There was a high level of heterogeneity between studies ( I 2 = 97.4%). Upon subgroup analysis, we found DCRs were higher in head trauma patients compared with traumatic cardiac arrest patients (45.3% vs 20.9%, p < 0.001), in pediatric patients compared with adults (61.0% vs 38.0%, p = 0.018), and in studies published after 2007 compared with those published before (50.8% vs 43.9%, p < 0.001). Few studies assessed for factors associated with OD in trauma patients. CONCLUSIONS: We found variation in DCRs among trauma patients (range, 14.0–75.2%) and estimated a pooled DCR of 48.1%. Our results are limited by heterogeneity across studies, which may be attributable to differences in study design and population, definitions of a POD, and in the institutional criteria and processes regarding OD. LEVEL OF EVIDENCE: Systematic reviews and meta-analyses level III. Abstract : Supplemental digital content is available in the text.